4‐allylanisole as a lure adjuvant for Dendroctonus frontalis (Coleoptera: Curculionidae: Scolytinae) and two associated beetles. (7th May 2022) - Sullivan, Brian T.; Munro, Holly L.; Shepherd, William P.; Gandhi, Kamal J. K.
Abstract: The southern pine beetle, Dendroctonus frontalis Zimmermann (Coleoptera: Curculionidae: Scolytinae), is a major pine tree killer in North and Central America. In the southeastern USA, responses by D. frontalis to its aggregation pheromone can be substantially increased by at least three host odours: the monoterpenes alpha ‐ and beta ‐pinene, and the phenylpropanoid 4‐allylanisole. We executed three trapping experiments to assess the influence of 4‐allylanisole release rate on aggregation behaviour of D. frontalis and to evaluate the compound as an adjuvant for the operational monitoring lure for D. frontalis . Addition of devices releasing 4‐allylanisole at any of three rates (4.8, 48, and 500 mg/day measured at mean 21°C) increased D. frontalis attraction to a pheromone lure, both in the presence and in the absence of an alpha ‐pinene lure. The increase was 5‐ to 50‐fold with a positive dose response up to the highest tested release rate of 4‐allylanisole. Attraction of an associate, the black turpentine beetle, Dendroctonus terebrans (Olivier), and a major D. frontalis predator, Thanasimus dubius (F.) (Coleoptera: Cleridae), was also significantly increased by 4‐allylanisole. A device releasing 4‐allylanisole at 0.05 g/day (at mean 23°C) increased attraction of D. frontalis to the current operational monitoring lure (which uses alpha ‐ and beta ‐pinene as the host odour component) approximately 4‐fold, but it did not increase attraction to a lure with turpentine as the host odour component (used in a former operational monitoring lure). Additionally, we observed none of the attraction‐inhibiting effects that were previously reported for 4‐allylanisole with D. frontalis . It is possible that the addition of 4‐allylanisole to the D. frontalis lure might allow detection of beetles at lower population densities and, if so, aid in earlier detection of populations invading the northeastern USA in response to climate change. This possibility should receive further investigation.